2020
DOI: 10.3390/jpm10040201
|View full text |Cite
|
Sign up to set email alerts
|

Altered Interoceptive Perception and the Effects of Interoceptive Analgesia in Musculoskeletal, Primary, and Neuropathic Chronic Pain Conditions

Abstract: Chronic pain (CP) severely disrupts the daily life of millions. Interoception (i.e., sensing the physiological condition of the body) plays a pivotal role in the aetiology and maintenance of CP. As pain is inherently an interoceptive signal, interoceptive frameworks provide important, but underutilized, approaches to this condition. Here we first investigated three facets of interoceptive perception in CP, compared with pain-free controls. We then introduce a novel interoceptive treatment and demonstrate its c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 113 publications
(210 reference statements)
5
37
1
Order By: Relevance
“…However, even before CT-fibres were discovered, it was suggested that Ab-fibres elicit allodynia following central sensitization in the dorsal horn, a notion that is also suggested by recent research (Liljencrantz & Olausson, 2014). This could explain why CT-optimal touch and skin vibration did not elicit a painful sensation in the study of Di Lernia et al (2020) and, more importantly, why CT-optimal touch reduced the experienced chronic pain. As described in the previous section and illustrated in Figure 3, pain modulation through the CT-system may depend on multiple neural mechanisms that may downregulate the possible overactivation of the ACC and PFC in chronic pain resulting in a decrease in experienced pain severity (Gursul et al, 2018;Krah e et al, 2016;Lu & Perl, 2003;Schmidt-Wilcke, 2015;von Mohr, Crowley, et al, 2018).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…However, even before CT-fibres were discovered, it was suggested that Ab-fibres elicit allodynia following central sensitization in the dorsal horn, a notion that is also suggested by recent research (Liljencrantz & Olausson, 2014). This could explain why CT-optimal touch and skin vibration did not elicit a painful sensation in the study of Di Lernia et al (2020) and, more importantly, why CT-optimal touch reduced the experienced chronic pain. As described in the previous section and illustrated in Figure 3, pain modulation through the CT-system may depend on multiple neural mechanisms that may downregulate the possible overactivation of the ACC and PFC in chronic pain resulting in a decrease in experienced pain severity (Gursul et al, 2018;Krah e et al, 2016;Lu & Perl, 2003;Schmidt-Wilcke, 2015;von Mohr, Crowley, et al, 2018).…”
Section: Discussionmentioning
confidence: 80%
“…Participants suffered from primary chronic pain, secondary musculoskeletal pain and neuropathic pain and received either CT-optimal touch or vibration on the skin. The effect of CT-optimal touch was independent of pathological condition (Di Lernia et al, 2020). Even in central and peripheral neuropathic pain its severity appears reduced by CT-optimal touch.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Chronic pain is an unpleasant sensory and emotional experience that persists or recurs more than three months and may extend beyond the expected time of healing [1,2]. Chronic pain occurs as a part of symptoms due to an underlying medical condition or remains despite successful treatment of the condition that originally caused it [3].…”
Section: Introductionmentioning
confidence: 99%